Model of the sustainable revitalization of the old industrial areas - Kokot Krajnc, Mojca (Journal for Geography, 2013)
Revitalizations of degraded areas, most of them are old industrial areas, have high potential for the implementation of the sustainable spatial development and protection of the green areas. The revitalization of them has to be sustainable planned and have to promoted social inclusion and new economic challenges. The current models of the sustainable revitalization of degraded areas are not fully realized this, because in the redevelopment are not equally involved all components. Paper presents a new model of the sustainable revitalization of old industrial areas, that comprehensively covers all components of development and they are causally and consequently related. It consists of four components: natural capital, sustainable society, local economy and material circuit. This model is realized by the revitalization of old industrial areas by the developing the eco industrial parks.